2014
DOI: 10.1002/jssc.201400871
|View full text |Cite
|
Sign up to set email alerts
|

Separation of triterpenoid saponins from the root of Bupleurum falcatum by counter current chromatography: The relationship between the partition coefficients and solvent system composition

Abstract: A separation method using counter current chromatography coupled with an evaporative light-scattering detection system was developed to purify five triterpenoid saponins from the roots of Bupleurum falcatum. The methanol extract was loaded onto a Diaion® HP20 column and fractionated by a methanol and water gradient elution. The saikosaponin-enriched fraction was obtained by elution with 100% methanol. The two-phase solvent systems used for separation were composed of chloroform/methanol/isopropanol/water at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…To obtain an efficient separation of target compounds, the previous articles on CCC demonstrated that the two‐phase solvent system should meet the following requirements: (i) sufficient sample solubility (<30 s); (ii) short settling time; (iii) appropriate partition coefficient ( K ) values (usually between 0.5 and 2); (iv) no decomposition or denaturation of the sample; and (v) satisfactory retention of the stationary phase. According to the previous reports, two‐phase solvent systems composed of n ‐hexane/ethyl acetate/methanol/water and light petroleum/ethyl acetate/methanol/water were widely used and also very efficient for CCC separation of polyphenol. The two‐phase solvent system was selected according to the K values of each target compound.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain an efficient separation of target compounds, the previous articles on CCC demonstrated that the two‐phase solvent system should meet the following requirements: (i) sufficient sample solubility (<30 s); (ii) short settling time; (iii) appropriate partition coefficient ( K ) values (usually between 0.5 and 2); (iv) no decomposition or denaturation of the sample; and (v) satisfactory retention of the stationary phase. According to the previous reports, two‐phase solvent systems composed of n ‐hexane/ethyl acetate/methanol/water and light petroleum/ethyl acetate/methanol/water were widely used and also very efficient for CCC separation of polyphenol. The two‐phase solvent system was selected according to the K values of each target compound.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our group found that SSa could induce the activation of various caspases and poly (ADP-ribose) polymerase (PARP), decrease Bcl-2 and X-linked inhibitor of apoptosis (XIAP) expression, and induce apoptosis in human colon carcinoma (HCC) cells [ 14 ]. In addition, SSa has been shown to have cytotoxicity against human gastric cancer, breast cancer, and hepatoma [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective CCC separation depends on the partition coefficient ( K D ) of each solute, and the K D values of the solutes depend on the selection of a suitable biphasic solvent system . Solvent mixtures of chloroform/isopropanol/methanol/water have frequently been used as the solvent system for the separation of saponins . Table shows the K D values and the settling time of each solute for solvent systems 1 to 6 as well as the phase ratio of the solvent system when the composition of the solvent system is varied.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the K D values and the settling time of each solute for solvent systems 1 to 6 as well as the phase ratio of the solvent system when the composition of the solvent system is varied. The addition of isopropanol afforded high K D values and prolonged the separation time of the compounds . However, an increase in isopropanol ratio caused a decrease in stationary phase retention, which is indicated by the increased settling time of the bi‐phase.…”
Section: Resultsmentioning
confidence: 99%